Peningkatan dan Perbaikan dari Temuan Audit External ISO 9001 di LP3I College - Wiwiet Prihatmadji (Majalah Ilmiah Bijak, 2019)
The findings of external audits in order to ensure the implementation of ISO 9001 quality management system at LP3I College for three consecutive years provide benefits in the form of improvement, correction  and consistency of the quality management system in accordance with applicable requirements. The methodology used refers to the PDCA methodology as a model for running the management process with continuous improvement. Improved system in the stages of the Plan in the form of Management of quality objectives, analysis and evaluation, as well as back up data. Stage of Do in the form of maintenance evaluation and realization of infrastructure and facilities targets, and Special Basic Skills Ability is set as a reference for the new admissions graduation Criteria. Stages of Check in the form of monitoring and evaluation of Quality Achievements by the leader of his subordinates, analysis and evaluation of customer satisfaction. The Act Stages are an evaluation of the effectiveness of Improvement Measures from the Non Conformance Report (NCR) findings, and makes corrective actions against any non-achievement of quality objectives. Corrections in the implementation of QMS as a solution of the findings by the auditor in the case of nonconformance of internal standards for Plan stage: document validation, re-examination of SOP content, and Evaluation on Outsourcing. For the cycle of Do: supplier evaluation responsibilities. While Check cycle: establishing observation findings as Auditor Suggestions or alternative improvements. Whereas the inconsistency actions that must be controlled so that they are always consistent in carrying out procedures include, stage of Plan : mapping each official according to his competence, stage of Do: the entire course and the recording, and stage of Check: the period of analysis and evaluation of customer satisfaction at least once a year.